Family Based Early Intervention Program for Language Development in Child of Attention Deficit Hyperactivity Disorder (ADHD) - Pratiwi Azizah Ekarani; Imas Diana Aprilia; Endang Rusyani (INCLUSIVE EDUCATION, 2023)
The research is aimed to optimize the development of the language of children with attention deficit hyperactivity disorder (ADHD) with designing program early interventions were given to the family. Subjects in the study this is a child with attention deficit hyperactivity disorder (ADHD) aged 4 years and the family of the child are. This study uses two research methods, a qualitative descriptive method with a case study research design and a quantitative method with a single subject experimental design (SSR). Procedure execution is doing preparatory research and studies preliminary through interviews, observations, and study documentation. Techniques of collecting the data in the study of this is to analyze the results of interviews, observations and studies documentation that has been done so that the gain profiles of children and families, carry out the preparation of the program, do the implementation of the program and evaluate the results of implementation. Results of the study stated that there is a change in the attitude of the parents and families in understanding the condition of the child, as well as having skills in optimizing development of languages of children attention deficit hyperactivity disorder (ADHD) by applying the program intervention early which has been designed.